Regulatory Interactions Between Neutrophils, Tumor Cells and T Cells - Oberg, Hans-Heinrich; Wesch, Daniela; Kalyan, Shirin; Kabelitz, Dieter (Frontiers in Immunology, 2019)
Apart from their activity in combating infections, neutrophils play an important role in regulating the tumor microenvironment. Neutrophils can directly kill (antibody-coated) cancer cells, and support other immune anti-tumoral strategies. On the other hand, neutrophils can also exert pro-tumorigenic activities via the production of factors which promote cancer growth, angiogenesis and metastasis formation. The balance of anti- and pro-cancer activity is influenced by the particularly delicate interplay that exists between neutrophils and T lymphocytes. In murine models, it has been reported that γδ T cells are a major source of IL-17 that drives the recruitment and pro-tumorigenic differentiation of neutrophils. This, however, contrasts with the well-studied anti-tumor activity of γδ T cells in experimental models and the anti-tumor activity of human γδ T cells. In this article, we first review the reciprocal interactions between neutrophils, tumor cells and T lymphocytes with a special focus on their interplay with γδ T cells, followed by the presentation of our own recent results. We have previously shown that zoledronic acid (ZOL)-activated neutrophils inhibit γδ T-cell proliferation due to the production of reactive oxygen species, arginase-1 and serine proteases. We now demonstrate that killing of ductal pancreatic adenocarcinoma (PDAC) cells by freshly isolated resting human γδ T cells was reduced in the presence of neutrophils and even more pronounced so after activation of neutrophils with ZOL. In contrast, direct T-cell receptor-dependent activation by γδ T cell-specific pyrophosphate antigens or by bispecific antibodies enhanced the cytotoxic activity and cytokine/granzyme B production of resting human γδ T cells, thereby overriding the suppression by ZOL-activated neutrophils. Additionally, the coculture of purified neutrophils with autologous short-term expanded γδ T cells enhanced rather than inhibited γδ T-cell cytotoxicity against PDAC cells. Purified neutrophils alone also exerted a small but reproducible lysis of PDAC cells which was further enhanced in the presence of γδ T cells. The latter set-up was associated with improved granzyme B and IFN-γ release which was further increased in the presence of ZOL. Our present results demonstrate that the presence of neutrophils can enhance the killing capacity of activated γδ T cells.